Escaping Air Pollution: Immigrants, Students, and Spillover Effects on Property Prices Abroad - Chang Y-Y; Dasgupta S (Oxford University Press)
We construct a time series of news coverage about air pollution in China for the period 1977-2019. Our measure of abnormal news coverage (ANC) of China's air pollution is uncorrelated with growth in economic activity or cyclical components of such activity, but strongly correlated with weather-related and atmospheric conditions known to cause air pollution. ANC is associated with more capital flight from China. Focusing on the USA as a destination country, we find that ANC is associated with more Chinese citizens emigrating to US regions with stronger ethnic links to China, and more international students enrolling in US institutions with stronger Chinese student links. US regions with stronger ethnic or educational ties to China experience higher property price growth when ANC is higher. Our study suggests that perception of local environmental risk can have major consequences for the cross-border reallocation of capital and labor. © 2022 The Author(s). Published by Oxford University Press on behalf of the European Finance Association. All rights reserved. For permissions, please email: journals.permissions@oup.com.
CAUL read and publish agreement 2022
Keywords: 1501 Accounting, Auditing and Accountability; 1502 Banking, Finance and Investment